Prophylactic treatment of Glycyrrhiza glabra mitigates COVID-19 pathology through inhibition of pro-inflammatory cytokines in the hamster model and NETosis - Rizvi, Zaigham Abbas; Babele, Prabhakar; Sadhu, Srikanth; Madan, Upasna; Tripathy, Manas Ranjan; Goswami, Sandeep; Mani, Shailendra; Kumar, Sachin; Awasthi, Amit; Dikshit, Madhu (Frontiers in Immunology, 2022)
Severe coronavirus disease (COVID-19) is accompanied with acute respiratory distress syndrome & pulmonary pathology, and is presented mostly with inflammatory cytokine release, dysregulated immune response, skewed neutrophil/ lymphocyte ratio, and hypercoagulable state. Though vaccinations have proved effective in reducing the COVID-19 related mortality, the limitation of use of vaccine against immunocompromised, comorbidity, and emerging variants remains a concern. In the current study we investigate for the first-time the efficacy of Glycyrrhiza glabra (GG) extract, a potent immunomodulator, against SARS-CoV-2 infection in hamsters. Prophylactic treatment with GG showed protection against loss in body weight and 35-40% decrease in lung viral load along with reduced lung pathology in the hamster model. Remarkably, GG reduced the mRNA expression of pro-inflammatory cytokines and Plasminogen activator inhibito-1 (PAI-1). In-vitro, GG acted as potent immunomodulator by reducing Th2 and Th17 differentiation and IL-4 and IL-17A cytokine production. In addition, GG also showed robust potential to suppress ROS, mtROS and NETs generation in a concentration dependent manner in both human polymorphonuclear neutrophils (PMNs) and murine bone marrow derived neutrophils (BMDNs). Taken together, we provide evidence for the protective efficacy of GG against COVID-19 and its putative mechanistic insight, which might be developed as a future immunomodulatory approach against various pathologies with high cytokine production, aberrant neutrophil activation including coronavirus infection.